Analisis Psikolinguistik Akuisisi Morfologi Bahasa Indonesia Pada Anak Sekolah Dasar: Faktor Kognitif Dan Lingkungan Belajar - Selfi Puspita Sari; Silvina Noviyanti; Nazurty; Nurul Huda Azkia; Renny Pita Rahmadani; Wahyu Yovika Hermawanti; Wita Septyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Psycholinguistic Analysis of Indonesian Morphology Acquisition in Elementary School Children: Cognitive Factors and Learning Environment is a literature study examining the development of Indonesian morphology in children aged 7-12 through a psycholinguistic lens. Employing a literature review methodology from Google Scholar, this research analyzes the interaction between cognitive factors (working memory, phonological awareness, metalinguistic awareness) and learning environments (home, school, digital media) in acquiring affixation, reduplication, and compounding. Key findings reveal a gradual progression: imitation in grades 1-2, generalization of inflectional affixes (me-, di-) in grades 3-4, and abstraction of derivational forms (pe-an) in grades 5-6. Cognitive factors accelerate the process by up to 40%, while rich narrative environments boost morphological vocabulary by 25-30%. Challenges include local dialect interference (Palembang, Javanese), overcrowded classrooms, and pandemic-induced limitations on verbal interaction. Practical recommendations include interactive teaching modules based on local folktales for the Merdeka Curriculum, teacher training in metalinguistic approaches, and home-school linkages. Theoretically, the study enriches models of agglutinative language acquisition in multilingual Indonesia, aligning with Krashen and Vygotsky theories. The primary contribution fills domestic research gaps to enhance elementary literacy, supporting SDG 4. Future research suggestions: empirical studies with eye-tracking post-pandemic.